Math, asked by shreya931754, 11 months ago

please anyone solve these questions and if you do not know please don't answer useless answers otherwise I will report them ​

Attachments:

Answers

Answered by ibranaaztechzx
0

25 (x + y)² - 36 (x - 2y)²

= {5 (x + y)}² - {6 (x - 2y)}²

= (5x + 5y)² - (6x - 12y)²

n

= (5x + 5y + 6x - 12y) (5x + 5y - 6x + 12y),

using the identity

a² - b² = (a + b) (a - b)

= (11x - 7y) (17y - x),

which is the required factorization.

#MarkAsBrainliest

q 2 attached in pic

plzz mrk me as brainliest ans plz

Attachments:
Answered by Anonymous
9

hey.... I am here to solve....✌️✌️✌️

Attachments:
Similar questions